GENERATION AND DIFFERENTIATION OF GROUP II KIMBERLITES: CONSTRAINTS FROM A HIGH-PRESSURE EXPERIMENTAL STUDY TO 10 GPA - Ulmer P.; Sweeney R.J. (My University, 2002)
Experiments have been performed in the multicomponent (natural) bulk system to constrain the conditions of generation and differentiation of a K-rich group II kimberlite (now also referred to as orangeite). The group II composition examined was saturated in olivine, orthopyroxene, and garnet at near liquidus conditions in the pressure range 4 to 10 GPa. In the range 2 to 3 GPa, the liquidus phase was olivine only. The potassic nature of the melts in the bulk compositions studied was ensured by the absence of any K-bearing phase in the residual assemblage at P > 4 GPa. Phlogopite is destabilized toward higher pressures by a carbonation reaction of the type phlogopite + CO2 = enstatite + garnet + K2CO3 (liquid) + H2O leading to alkalic, carbonatitic liquids coexisting with a garnet–peridotite (harzburgite or lherzolite) residue over a wide pressure–temperature space at pressures in excess of 4 GPa. Evidently, CO2-bearing systems do not favor the stability of phlogopite and/or K-richterite amphibole at pressures in excess of 4 to 5 GPa, and it is suggested that the carbonate-bearing and potassic character of any mantle melt originating from this depth is most likely the product of a two-stage process: either a carbonate-bearing protolith is invaded by a potassic melt or fluid (probably supercritical), or a potassic protolith (after metasomatism) has been invaded by a carbonatite melt.